EFFECT OF TRACE ELEMENT SUPPLEMENTATION ON THE GASTROINTESTINAL PARASITES OF GRAZING SHEEP - S. Ahmad; M. S. Sajid; 2; M. K. Khan; R. Nadeem; H. M. Rizwan; M. A. Malik; F. Yosuf (Journal of Animal and Plant Sciences, 2020)
Alternative gastrointestinal (GI) parasite control strategies including phytomineral/ trace-element supplementation have gained currency in preview of anthelmintic resistance in the grazing sheep. This paper reports an association of the selected plants/ forages having optimum levels of Zinc (Zn), Copper (Cu), Manganese (Mn) and Cobalt (Co) on the GI parasitic burden in sheep and hence on the productive performance of the grazing sheep of Multan district, Punjab, Pakistan. To this end, levels of trace elements were determined in the plants/ forages preferred by the grazing sheep, and in the sera of randomly selected grazing sheep (n =384). Serum trace element profile was correlated with the GI parasitic burden to determine the possible impact of trace-elements on GI parasitic load. After pre-treatment, wet digestion of sera and plants, concentration of the selected minerals (Cu, Co, Zn and Mn) were measured using spectrophotometry. Faecal samples (n=384) were subjected to the quantitative faecal examination using McMaster technique. Overall 42.44% prevalence of GI parasites was found in the study population. Of the eight screened forages, Cynodon dactylon, Launaea nudicaulis and Digitaria sanguinalisshowed top three levels of Mn in decreasing order. Comparative mineral profile of sera was significantly different among the four tehsils (administrative units) of Multan district, Punjab, Pakistan. Mn showed significant correlation with the egg per gram (EPG) of faeces in sheep of tehsil Shujabad, whereas, Cu, Zn and Co showed insignificant results in all tehsils of Multan district. Further research is needed to explain the possible mechanism involved in the role of Mn in the indirect resilience of animals against the GI parasites. These forages might be preferred as holistic approach and possible use as a preventive management of GI parasitism in grazing sheep of the country.
Keywords: Multan; Sheep; Forages; Gastrointestinal parasitism; Phytominerals; Sera samples; Trace elements